Use of online safety decision aid by abused women: effect on decisional conflict in a randomized controlled trial - Eden, Karen B; Perrin, Nancy A; Hanson, Ginger C; Messing, Jill T; Bloom, Tina L; Campbell, Jacquelyn C; Gielen, Andrea C; Clough, Amber S; Barnes-Hoyt, Jamie S; Glass, Nancy E (American journal of preventive medicine, 2015)
An Internet safety decision aid was developed to help abused women understand their risk for repeat and near-lethal intimate partner violence, clarify priorities related to safety, and develop an action plan customized to these priorities. To test the effectiveness of a safety decision aid compared with usual safety planning (control) delivered through a secure website, using a multistate RCT design. The paper evaluates the effectiveness of the safety decision aid in reducing decisional conflict after a single use by abused women. RCT referred to as Internet Resource for Intervention and Safety (IRIS). Abused women who spoke English (n=708) were enrolled in a four-state RCT. The intervention was an interactive safety decision aid with personalized safety plan; the control condition was usual safety planning resources. Both were delivered to participants through the secure study website. This paper compares women's decisional conflict about safety: total decisional conflict and the four subscales of this measure (feeling: uninformed, uncertain, unsupported, and unclear about safety priorities) between intervention/control conditions. Data were collected from March 2011 to May 2013 and analyzed from January to March 2014. Immediately following the first use of the interactive safety decision aid, intervention women had significantly lower total decisional conflict than control women, controlling for baseline value of decisional conflict (p=0.002, effect size=0.12). After controlling for baseline values, the safety decision aid group had significantly greater reduction in feeling uncertain (p=0.006, effect size=0.07) and in feeling unsupported (p=0.008, effect size=0.07) about safety than the usual safety planning group. Abused women randomized to the safety decision aid reported less decisional conflict about their safety in the abusive intimate relationship after one use compared to women randomized to the usual safety planning condition.